Determinants of employee turnover intention in Samsung Corning Precision Materials (M) Sdn. Bhd. / Nurliyana Annisa Zulkifli - Zulkifli, Nurliyana Annisa (Faculty of Business and Management, 2014)
This research is conduct to carry out “Determinants of employee turnover intention in Samsung Corning Precision Materials (M) Sdn Bhd”. The main objective is to measure and identify the most factor that influencing employee’s intention to quit in the organization. It consists of three (3) factors which are work environment, job satisfaction and organization commitment. At this research nonprobability sampling techniques and simple random techniques were used to get the data required. Population of the research was employees of Samsung Corning Precision Materials (M) Sdn Bhd and the sampling frame is the employee of Samsung Corning Precision Materials (M) Sdn Bhd, Senawang. About 70 from 80 respondents were getting from the research to help for accomplish this research by answering the questionnaires that had been distributed to them. All the data collected through the questions were analyzed systematically by using Statistical Package for Social Science (SPSS). The conclusion of this study was the outcomes from the data analysis and findings. Through the research, a clear finding and results are observed. The finding showed work environment is the most factors that contribute turnover in the organization.